The development of automotive basic technology e-modules for students of automotive light vehicle engineering - Hasan MD, Zaenul; Setuju, Setuju; Samidjo, Samidjo; Gunawan, Teddy Surya (Universitas Sarjanawiyata Tamansiswa, 2024)
Abstract: This research aims to obtain a decent E-Module in the Basic Automotive Technology subject of Class X Automotive Light Vehicle Engineering Students at SMK Muhammadiyah Mlati Sleman for the 2023/2024 Academic Year. This research is an R&D Research and Development research that uses the ADDIE model with stages of Analysis, Design, Development, Implementation and Evaluation. with the sources of this research data are (1) Material Expert validators, (2) Media Experts, and (3) Students. Data collection method using Observation, Questionnaire and Documentation. Data analysis of this study uses the Kuantitatif technique and uses a percentage scale, namely calculations in data analysis will produce percentages. The percentage calculation process is carried out by the number of values obtained and divided by the maximum score then multiplied by one hundred percent. The results of the study showed that the feasibility level in material validation was obtained a score of 95% in the very feasible category, media validation was obtained a score of 74% in the feasible category, small-scale product trials in students obtained a score of 94% in the very feasible category, and large-scale trials obtained a score of 90% in the very feasible category Keywords: Development, E-module, Learning, TDO